Scope And Implementation Of Fssai Standards - In Free Standing Restaurants (PUSA Journal of Hospitality and Applied Sciences, 2015)
Background: The current study on "Scope and Implementation of FSSAI Standards"- in free  standing restaurants was done with the aim of studying the aspects of food safety in restaurants in  Delhi NCR. Objective: The objective of the study was to find out the implementation of FSSAI  standards by restaurants. Methods: Restaurants were selected through random sampling. Checklist  was administered in order to find out the existing scenario of FSSAI standards. Result: It was  observed that only 17% of the restaurants were following FSSAI Standards.
Keywords: FSSAI; Food Safety Practices; Checklist